Implementasi Strategi Kepemimpinan Kepala Madrasah dalam Optimalisasi Kinerja Guru pada MTs Negeri 2 Kota Jambi - Mutingatussholikah Mutingatussholikah (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2023)
This study aims to analyze the leadership strategies implemented by the principal in improving teacher performance at Madrasah Tsanawiyah Negeri 2 Kota Jambi. A qualitative interactive approach was employed, with data collected through observation, in-depth interviews, and documentation. The findings reveal that, first, teacher performance at MTsN 2 Kota Jambi has not yet reached an optimal level. This is indicated by the lack of punctuality among some teachers and their limited awareness of responsibilities beyond classroom teaching, including contributing to the overall development of the institution. Second, the principal applies several leadership strategies to enhance teacher performance, such as engaging in training and professional development, conducting continuous supervision, providing motivation, and strengthening discipline. Third, challenges faced by the principal include the limited awareness of teachers to contribute more significantly to the school’s progress and inconsistent discipline due to individual workload and personal busyness. Overall, this study highlights that the effectiveness of the principal’s leadership strategies plays a significant role in improving teacher performance, despite the persistent challenges that require continuous solutions.